Work-Related Risk Factors for Lateral Epicondylitis in Chef in Lahore - Fareeha Amjad, Mehak Matloob, Noor Ul Nisa Javed, Adnan Hashim, Ammara Chaudhry, Bisma Zafar, Kanza Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Numerous cross-sectional epidemiological studies on the incidence of workplace epicondylitis have generally, but not always, revealed a higher risk of the ailment in relation with strenuous manual tasks. Methods: A cross-sectional study was conducted in Lahore. The data was acquired from chefs who worked in different restaurants. The research used a Patient-Rated Tennis Elbow Evaluation as its survey method (PRTEE). Participants also received a consent form and a questionnaire. A different T-test was applied. In order to analyses the data, SPSS version 25 was used. Results: Among the 136 participants, 29 (21.3%) were women, and 107 (78.7%) were men. The frequency and proportion of participants’ dominant hands are shown on this graph: 48/136 (35.3%) and 88/136 (64.7%) of the 136 people had left hands. 32/136 (23.5) of the participants reported their level of discomfort while at rest, while 52/136 (38.2) reported mild pain and 20/136 (14.7) reported severe pain. While making repetitive arm motions, 161/136 (11.8) respondents reported no pain, 50/136 (36.8) minor discomfort, 59/136 (43.4) moderate discomfort, and 11/136 (8.1) severe discomfort. Only six out of 136 respondents (4.4%) said they weren’t uncomfortable, as opposed to the 53 (39.0%), 57 (41.9%), and 20 (14.7%) who claimed carrying a plastic bag caused them slight to severe pain. According to this graph, participants who experienced the least amount of pain reported no pain in 32/136 (23.5) cases, mild discomfort in 7/136 (5.1) cases, moderate pain in 66/136 (48.5) cases, and severe pain in 38/136 (27.9) cases. Using a doorknob or key caused 90/136 (66.2%) people no pain, 22/136 (16.2%) moderate pain, 22/136 (16.2% discomfort), and 7/136 (5.1%) severe pain, according to this graph. This study was conducted to create the awareness in chef to avoid from risk factors of epicondylitis. Conclusion: As a result, it was established that chefs experienced pain on the lateral side of either their dominant right hand or left hand for a variety of reasons. Repetitive motions, recreational activities, and housework are all causes. On the lateral side of their right hand, which is more frequent in women, they experience a small stiffness. Keywords: Patients’ Evaluation of Tennis Elbow, Lateral Epicondylitis, and Myotendinosis (PRTEE).